Economic State-Building and the Regulation of FDIs in Kosovo: Reconciling Economic Sovereignty and Conditionality - Cristani, Federica (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2014)
Annotation: The present paper aims at defining the concept of economic sovereignty in the framework of processes of State-building, with particular regard to the regulation of foreign direct investments (FDIs). Firstly, it addresses the definition of the concept of «economic sovereignty» and its development, with particular regard to countries facing processes of economic reconstructions (like post-conflict and transitional situations). In this respect, attention will be devoted to the concept of «conditionality», as first developed by the International Monetary Fund (IMF) within its supporting programs and then used by the European Union (EU) for its enlargement policy. The analysis will focus on the Western Balkans and in particular to Kosovo: the Kosovo case study sums up various aspects of external influences on a country’s governance. Taking into account the role of EU conditionality in the exercise of the economic sovereignty of Kosovo, the main question to be answered is whether there is an ‘erosion’ of economic sovereignty or simply a reconfiguration of the relationship between national economic policies and EU policies, with particular regard to the definition of a domestic legal framework for investment protection. Key words: Economic sovereignty, state-building, post-conflict reconstruction, economic reconstruction, investment protection, economic conditionality, globalization, Kosovo, EU Stabilisation and Association Process, EULEX mission.